From Semanalysis to Intertextuality in the Song “Kalām ‘Aynīh”: A Julia Kristeva Perspective - Noriska, Zacky Aqsha; Zulkhairi, Zulkhairi; Zulhelmi, Anshar; Razak, Abd; Azwir, Azwir (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2026)
This study aims to uncover the meaning of the lyrics yā layl yā laylī in the song kalām ‘aynīh through Julia Kristeva’s semiotic analysis. This research employs a qualitative descriptive method, utilizing written data in the form of the song lyrics of kalām ‘aynīh and netizen comments from several TikTok accounts. The data collection technique applied in this study is a note-taking and reading technique through a literature review. The data are analyzed through the stages of identification, application, analysis, and conclusion drawing. The findings indicate that the genotext is understood as an inner process encompassing feelings of love, longing, and emotional experiences, which are then expressed through the song lyrics, while the phenotext is manifested in the lyrics of Kalam Eineh that function to convey the meaning of the genotext. At the level of signification, the lyrics yā layl yā laylī signify longing for the presence of the beloved, whereas at the level of signifiance they convey an idealized specification of the female figure. Intertextually, the lyrics yā layl yā laylī represent longing for one’s beloved. Thus, the interpretation of the lyrics yā layl yā laylī provides an explanation for the shift in meaning that occurs in kalām ‘aynīh has interpreted by TikTok users in Indonesia, while simultaneously emphasizing the importance of a comprehensive and contextual understanding of song lyrics so that the meanings received remain grounded in the original text.